The subject inflections of the Mek languages: a comparative reconstruction - Edgar Suter (Nusa, 2021)
The Mek languages are a family of Papuan languages spoken in the eastern highlands of the Indonesian province Papua. They have a rich verb morphology with subject and object indexation and numerous temporal, modal, and aspectual categories. In this paper, I focus on the subject inflections, which are combined with tense or mood. Six paradigms of subject person-number endings are reconstructed. In addition, I reconstruct the personal pronouns. Shared innovations that emerge from the reconstructions are used to subgroup the Mek languages.